Collaboration or Coercion? Partnering to Divert Prescription Opioid Medications. - Green, Traci C; Bowman, Sarah E; Ray, Madeline; Zaller, Nickolas; Heimer, Robert; Case, Patricia (Journal of urban health : bulletin of the New York Academy of Medicine, 2013)
Diversion of prescription opioids is a widespread problem in the USA. While "doctor shopping" and pill brokering are well-described types of medication diversion, we sought to understand the social dynamic of diversion of prescription opioids and identify other diversion methods. Using qualitative data collected as part of a 12-week Rapid Assessment and Response study of prescription opioid overdose and abuse (the RARx Study) conducted in three communities in two New England states, we reviewed and thematically coded 195 interviews. Diversion took many forms: doctor shopping, pill brokering, and, most commonly, siphoning from the family medicine chest. Partnering-of patients with other "patients," of patients with "caregivers"- to obtain prescription opioids was also described. Motivations for partnering indicated doing so out of fear of violence, for financial benefit, or in exchange for transportation or other services. Partnering for prescription opioids exhibited a range of power differentials, from collaboration to coercion, and tended to involve vulnerable populations such as the elderly, disabled, or destitute. Increased awareness among health providers of the ease of access and diversion of prescription opioids is needed to promote patient safety and prevent interpersonal violence.